ChemInform Abstract: Recyclable Palladium(II) Imino‐Pyridine Complex Immobilized on Mesoporous Silica as a Highly Active and Recoverable Catalyst for Suzuki—Miyaura Coupling Reactions in Aqueous Medium. Issue 23 (16th May 2013) - Zhang, Qiang; Su, Hong; Luo, Jun; Wei, Yunyang
Abstract Tosyl, mesyl as well as chloro leaving groups are not applicable.